A Measure of Competitive Access to Destinations for Comparing Across Multiple Study Regions. Issue 1 (7th January 2019) - Allen, Jeff; Farber, Steven
Abstract : Accessibility is now a common way to measure the benefits provided by transportation–land use systems. Despite its widespread use, few measurement options allow for the comparison of accessibility across multiple urban systems, and most do not adequately control for market competition between demand‐side actors and supply‐side facilities in localized markets. In this article, we develop a measure of competitive access to destinations that can be used to accurately compare accessibility between regions. This measure stems from spatial interaction modeling and accounts for competition at both the supply and demand sides of analysis, regional differences in transportation networks and travel behavior, and any imbalance between the size of the population and the number of opportunities. We use this method to compute access to employment for Canada's eight largest cities to comparatively examine inequalities in accessibility, both within and between cities, and by travel mode.